FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI RT/007 RW/008 DESA AIR DINGIN KECAMATAN BUKIT RAYA PEKANBARU - Heni Heriyeni; Rizki Natia Wiji (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
In Indonesia, diarrheal disease is one of the causes of death in infants. Diarrhea is one of the most common diseases affecting children worldwide. The aim of the study was to determine the factors associated with the incidence of diarrhea in toddlers at RT007 RW008 Airdinding Village, Bukit Raya District, Pekanbaru in 2024. This research method used an analytical survey approach with a cross sectional design. The population in this study were all babies who visited the Simpang Tiga Health Center as many as 126 toddlers. Sampling was carried out by Probability Sampling with a total of 95 samples. Primary data collection using a questionnaire. Univariate analysis described the frequency distribution of each variable while bivariate analysis used the Chi-Square test. The results of univariate analysis showed a history of non-exclusive breastfeeding 51.6%, 65.3% less knowledge of mothers, 57.9% personal hygiene and 67.4% history of diarrhea and the results of bivariate analysis showed that there were three variables of history of exclusive breastfeeding with p value = 0.0016, mother's knowledge p = 0.000 and maternal personal hygiene with p = 0.000 means that Ho is rejected and Ha is accepted. It is suggested that health workers at the Simpang Tiga Health Center provide promotions that should be focused on eliminating various inaccurate assumptions about diarrhea. Diarrhea prevention promotion materials should include the influence of the environment and breastfeeding on the occurrence of diarrhea with the process of activities being carried out in an integrated manner with the planning of other programs.